B-2b=b+4b+2

Simple and best practice solution for B-2b=b+4b+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for B-2b=b+4b+2 equation:


Simplifying
B + -2b = b + 4b + 2

Reorder the terms:
B + -2b = 2 + b + 4b

Combine like terms: b + 4b = 5b
B + -2b = 2 + 5b

Solving
B + -2b = 2 + 5b

Solving for variable 'B'.

Move all terms containing B to the left, all other terms to the right.

Add '2b' to each side of the equation.
B + -2b + 2b = 2 + 5b + 2b

Combine like terms: -2b + 2b = 0
B + 0 = 2 + 5b + 2b
B = 2 + 5b + 2b

Combine like terms: 5b + 2b = 7b
B = 2 + 7b

Simplifying
B = 2 + 7b

See similar equations:

| 3(y-4)= | | 4x+8/4-2=x | | 2x^2-4x/x-2 | | 8+7x+4x=63 | | x+6=x.4 | | 99x+65=-4x | | z(4x^10y^11z^8)= | | 7+3C=-7 | | .25n=2n-21 | | 5(2x-12)+21=2x+21 | | w=4x(y-5) | | 210(-3)= | | 2(3+x)=20+3x | | 9y+2=11y+8 | | z(16xy^3z^3)= | | e^4y-ln(y^2+3)=2x | | Yy-2=y+1y-5 | | 27x^2-54x+2805=0 | | x+8=-2-2+5x | | 2w-4=2 | | 2w-4= | | k=11+9-8+99 | | -6x+8=6x+8 | | 17+b= | | log(5*3)= | | G(f(3))+g(g(8))= | | 5a-5+4a+8=10a+40 | | z(4x^10y^11z^8)*z(16xy^3z^3)= | | 3f-8=6+f | | 7x^2+2x-13=0 | | 5sqrt(4x^10y^11z^8)*5sqrt(16xy^3z^3)= | | 3s+2=5s+8 |

Equations solver categories